PENGARUH LAUGHTER THERAPY TERHADAP ANSIETAS MAHASISWA TINGKAT I STIKes SANTA ELISABETH MEDAN TAHUN 2016 - Mestiana Br Karo (Elisabeth Health Jurnal, 2016)
Background: Anxiety is a feeling that can be experienced by anyone, such as anxiety during examination, anxiety when talking ahead of the crowd and others. So also with students, where students experience a transition from adolescence to adulthood. Students have many tasks to learn and start thinking about their future. All of these can make the student vulnerable enough to experience anxiety. Excessive anxiety can disrupt the learning process so as to reduce student achievement. For that we need a way to overcome it, one of them is laughter therapy. Laughter therapy is an antidote to stress, pain and cause excitement.Goals: This study aims to determine the influence of laughter therapy on anxiety in the freshman of STIKes Santa Elisabeth Medan.Methods:The research used one group pre test and post test design. Sampling technique with quota sampling method as many as 11 people from DIII Nursing, 14 people from DIII Midwifery and 38 people from Ners. Instruments used for data retrieval are SOP (Standard Operational Procedure) and observation sheet.Result: The result of the research showed that pretest ansietas was in moderate level of 46 people (73%) and posttest at light level of 42 people (66,7%). Data analysis was done by using Wilcoxon Sign Rank Test with p= 0,000 (<0,05).Conclussion: The conclusion is the effect of laughter therapy on the anxiety of first grade students. Suggestions are given so that the students do laughter therapy regularly to reduce the level of anxiety so that they will feel relaxed.